NORMATIVITY UNDER MARKET PRESSURE: THE JURISPRUDENTIAL LIMITS OF SHARIAH COMPLIANCE IN ISLAMIC FINANCE - Fatima Malik; Ahmed Shah; Oliver Harris (Sharia Oikonomia Law Journal, 2026)
Islamic finance has expanded within increasingly competitive global markets, intensifying tensions between Shariah normativity and economic pragmatism. Contemporary practices often prioritize formal compliance, raising concerns about whether legal structures genuinely reflect underlying ethical principles. This study aims to examine the jurisprudential limits of Shariah compliance by analyzing how market pressures influence legal reasoning and the construction of permissible financial practices. A qualitative normative–juridical research design is employed through systematic analysis of 96 legal documents, including fatwas, regulatory frameworks, and international standards across multiple jurisdictions. Analytical matrices and thematic coding are used to identify patterns of normativity, compliance, and market adaptation. The findings reveal that Shariah compliance operates as a dynamic spectrum, where hybrid frameworks dominate by balancing formal legality with market competitiveness. Normative alignment tends to weaken under high market pressure, leading to selective interpretation of jurisprudential principles. Institutional governance plays a critical role in mediating this tension, with centralized systems showing greater resistance to purely market-driven adaptations. The study concludes that Shariah compliance cannot be equated with substantive normativity and must be reconceptualized as a negotiated process shaped by jurisprudential flexibility and economic constraints.